Cleaning Puparia for Forensic Analysis. Issue 5 (4th July 2016) - Higley, Leon G.; Brosius, Tierney R.; Reinhard, Karl J.; Carter, David
Abstract: We tested procedures for removing adipocere from insect samples to allow identification. An acceptable procedure was determined: (i) Samples were sorted in petri dishes with 75% alcohol to remove any larvae, adult insects, or other soft‐bodied material. (ii) Samples of up to 24 puparia were placed in a vial with 15 mL of 95% acetone, capped, and vortexed for a total of 30–90 sec in 10‐ to 15‐sec bursts. This step removed large masses of adipocere or soil from specimen. (iii) Specimens were removed from acetone and placed in a vial of 15 mL of 2% potassium hydroxide (KOH) and vortexed in 10‐ to 15‐sec bursts until all puparia appeared clean (with our samples this required a total of 60–120 sec). (iv) Specimens were removed from the 2% KOH, placed in 75% ethanol, and examined microscopically. (v) Material was stored in 75% ethanol for identification and long‐term preservation.